2005
DOI: 10.1038/sj.bjc.6602426
|View full text |Cite
|
Sign up to set email alerts
|

Australian experience of a modified schedule of FOLFOX with high activity and tolerability and improved convenience in untreated metastatic colorectal cancer patients

Abstract: This study determined the efficacy and safety of a modified FOLFOX regimen that improved patient convenience without compromising oxaliplatin dose intensity. A total of 62 patients with previously untreated metastatic colorectal cancer were enrolled to receive, entirely as outpatients, 2-weekly cycles of oxaliplatin 100 mg m À2 i.v. over 2 h, together with leucovorin 400 mg m À2 over 2 h, 5-fluorouracil (5-FU) 400 mg m À2 , bolus, followed by a 46-h infusion of 5-FU at 2.4 g m À2 . Treatment was given until pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Furthermore, the median RD (9.2 months) and median PFS (8.6 months) were comparable with those usually observed with L-HOP-based combinations [1, 9,14]. However, the low progressive disease rate (9.4%) and the high percentage of patients that went on to surgical resection of metastases (15.6%) perhaps may reflect a better than average group performance with regard to patient selection, as is always the hazard of phase II trials.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Furthermore, the median RD (9.2 months) and median PFS (8.6 months) were comparable with those usually observed with L-HOP-based combinations [1, 9,14]. However, the low progressive disease rate (9.4%) and the high percentage of patients that went on to surgical resection of metastases (15.6%) perhaps may reflect a better than average group performance with regard to patient selection, as is always the hazard of phase II trials.…”
Section: Discussionsupporting
confidence: 48%
“…In a recent multicenter randomized trial, severe neurotoxicity was observed in 18% of patients after a median of 12 FOLFOX-4 cycles; the median PFS was 8.7 months [14]. Another recent study about a modified FOLFOX regimen, in which L-HOP was used at a dose of 100 mg/m 2 , reported comparable PFS (8.2 months), but a higher incidence of severe neurotoxicity (21%) compared to our population study [9]. …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A FOLFOX-4 regimen was identified as a tolerable and effective therapeutic modality in cases of advanced gastric cancer. Response rates range from 39 to 56%, TTP is from 5.2 to 7.1 months, and the median OS is between 8.6 and 11.4 months [3,8,12,18,19,20]. Despite the current numerous efforts of randomized trials in unresectable advanced or recurrent gastric cancer patients treated with the FOLFOX-4 regimen, only limited, globally accepted standard data have been established.…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective agent with a different toxicity profile for the treatment of advanced gastric cancer patients in several phase II studies [9,10,11]. The combination of oxaliplatin, 5-FU and leucovorin (FOLFOX) has been the standard treatment for patients with metastatic or advanced colorectal cancers [12]. In comparison with cisplatin, FOLFOX has a low-toxicity profile, with substantially lower rates of myelosuppression, nephrotoxicity and ototoxicity but with at least equivalent antitumor activities [13].…”
Section: Introductionmentioning
confidence: 99%